Obstetric care - Olsen, Martin (Cambridge University Press, 2017)
Gain a critical understanding of obstetrics, and a thorough knowledge base of modern management techniques, with this accessible textbook. While acting as a stand-alone text on obstetric care, this volume also forms part of a three-volume set - all authored by leading authorities - on the entirety of obstetric and gynecologic practice. Obstetric Care's topics are based on academic objectives of experts in the field. This textbook offers tailored support for new residents and experienced physicians alike. Obstetric Care is invaluable for wide-ranging yet concise reference material, and provides evidence based care recommendations for specific patient conditions. The chapters in this textbook are based on the objectives of the Committee for Resident Education in Obstetrics and Gynecology; the book offers outstanding modern management techniques across the obstetrics specialty, making it a go-to for reference and comprehensive study
Title from publisher's bibliographic system (viewed on 29 Sep 2017)
Keywords: Obstetrics; Geburtshilfe; Schwangerschaft